FNAC and histopathological correlation of salivary gland lesions: an observational study - Kakoty, Sneha; Baruah, Tridip Dutta; Babu, C. P. Ganesh (International Surgery Journal, 2017)
Background: Fine needle aspiration cytology (FNAC) is a sensitive and specific and yet an economically effective technique for diagnosis of salivary gland lesions. FNAC of salivary glands has achieved a pivotal role in the diagnosis and management of salivary gland lesions since its induction by Stewart et al in 1933. However, it has always been under scrutiny when compared to histopathology. Histopathology of salivary gland lesions is still the final method to establish diagnosis and predicting prognosis in these lesions.1 Methods: A prospective observational study of 50 patients with salivary gland lesions was done at Gauhati Medical College and hospital from June 2011 to May 2012. 39 patients underwent histopathological confirmation. Cases with histopathological correlation were included in calculating diagnostic accuracy. The cytological findings were correlated with that of the histopathological diagnosis to obtain the accuracy of the cytological diagnosis. The parameters of diagnostic validity of the cytological technique in terms of sensitivity, specificity and predictive value were evaluated. Results: Study population included patients of age group ranging from 13-70 years with median age group being 31-40 years (30%). 54% of the affected patients were male with the parotid being the most commonly involved gland (62%). Neoplastic lesions constituted the major bulk of the lesions (39 cases, 78%) with benign tumours constituting 54%. The most commonly involved benign neoplastic lesion was pleomorphic adenoma (22cases, 44%). Among the non-neoplastic lesions (22%), the acute sialadenitis was frequently noted. Histopathological correlations were available in 39 cases with 11 cases being the malignant lesions. The acute sialadenitis lesions did not undergo histological examination. 28 cases of non-malignant lesions underwent the histological confirmation. In the present study, the specificity and the sensitivity were found to be 96.42% and 90.91% respectively. The predictive value of salivary gland cytology was 90.91% and diagnostic accuracy was 94.87%. Conclusions: Fine Needle Aspiration Cytology is thus a safe, reliable, quick, convenient and accurate method of diagnosis and should be considered as one of the first line of investigations in the evaluation of salivary gland lesions.